21st Century Administrative Skills of School Administrators Chonburi Meung Campus 1 Chonburi Primary Educational Service Are Office 1 - เคนน้อย, อภิวัฒน์; น้อยมณี, นิวัตต์; ภูวนัย สุวรรณธารา, ภูวนัย สุวรรณธารา; ธรรมศิริ, สุภาพร; เลวัลย์, นำชัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purposes of this research were 1) to study the  century administrative skills of school administrators Chonburi meung campus 1 Chonburi primary educational service area office 1, and 2) to compare the  century administrative skills of school administrators Chonburi meung campus 1 Chonburi primary educational service area office 1. The sample group used in this research was 140 teachers in Chonburi meung campus 1 Chonburi primary educational service area office 1, academic year 2023. The sample group size was acquired by the samples group size was using Krejcie & Morgan's table. Then a stratified sampling and Simple random sampling. Statistics used in the research include by using frequency, percentage, mean and standard deviation, t-test, and one way analysis of variance.The research results were 1)  century administrative skills of school administrators Chonburi meung campus 1 Chonburi primary educational service area office 1. Overall a high level. When considering each aspect, it was found that the first average is Creative thinking skills, followed by communication skills and the last ranking is Human relations skills. 2) The comparison results  century administrative skills of school administrators Chonburi city campus 1 Chonburi primary educational service area office 1. Classified by gender, education level, age, and working experience. found that overall were not statistical significance.